"Effect of temperature x THI on acclimatization in buffaloes subjected to simulated heat stress: physio-metabolic profile, methane emission and nutrient digestibility". Issue 10 (26th November 2021) - Wankar, A. K.; Singh, G.; Yadav, B.
ABSTRACT: The study was conducted on four adult murrah buffaloes to evaluate the acclimatization process during simulated thermal stress. The animals were exposed to 25, 30, 35 and 40°C in climatic chamber, daily for five hours for 21 days at each treatment. Physiological variables i.e. respiration rate (RR), rectal temperature (RT) and pulse rate (PR) were recorded daily, while blood collection was done every fifth day for biochemical and hormonal estimation. Digestibility trial (apparent) and methane collection was performed during last four days at all the treatments. The physiological variables increased significantly at 35°C and 40°C as compared to other treatments ( P < 0.05). An increase in feed intake, dry matter and ether extract digestibility was confirmed while, the average methane emission decreased during heat stress than at optimum temperatures. Thyroid hormones declined and glucocorticoids increased at 35°C and 40°C. A decrease was also recorded for urea nitrogen and creatinine but, total protein and albumin initially decreased and then increased back to pre stress levels at 40°C. The physiological responses are immediately activated as acclimatory process followed by metabolic, digestive and endocrinal changes aimed at systemic acclimatization. It was observed that, for successful homeorhetic and homeostatic response to multi-stressors the buffaloes require more than 21 days acclimatization period.